The mirage of European governance: how to resolve the "puzzle" of EU Enlargement - Taulant Hasa (London School of Economics and Political Science (LSE), European Institute, 2021)
The eurozone debt and economic crisis, which the EU is still struggling to overcome, opened other paths for European Governance. Moreover, Brexit and the COVID-19, have been added to other EU challenges such as climate change, security and radicalism, migration flows, and lastly public health emergencies. To a lesser extent, but with a direct approach on the capacity of the EU as a global actor and its "soft power", enlargement has been a controversial but effective tool to enhance the EU as a global actor. The challenges listed above have displaced the focus on enlargement, at the same time eroding the ability of the European model to emerge beyond its borders. The enlargement in southeast Europe has entered a spiral of different perspectives among Member States, affecting the efficiency of the European Governance in this region. Although this area represents less than 1% of the EU economy, the "ability" of distortion may question the claim of the EU as a global actor.
Keywords: 330; European Governance; Western Balkans; Enlargement; Integration